DAYA TARIK WISATA PANTAI BATU LIMAU SEBAGAI DESTINASI WISATA KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Putri, Dian Seftiani; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Batu Limau Beach is a beach tourism in Ungar District, this research aims to find out the description of the attraction of beach tourism in Batu Limau Beach and the efforts of the local government regarding the attraction of beach tourism in Batu Limau Beach. This study uses a qualitative method with a descriptive approach. The subjects of this study are tourists, the Batu Limau Village Government, Batu Limau Beach tourism business actors, Batu Limau Village Youth Organization, and the local community. This research was carried out using data collection techniques in the form of observation, interviews, and documentation. The results of this study show that Batu Limau Beach has a beach tourist attraction in the form of unique and interesting rocks. Around the beach there are many unique rocks that resemble human life forms. The Government's efforts to develop the Batu Limau Beach Attraction still have many shortcomings in terms of facilities and promotion of tourist attractions. Keywords : attraction, tourism, batu limau beach